Muscle strength and quality of life improved after vitamin D supplementation among adult Saudi females. (August 2019) - Ewid, Mohammed; AlTelbany, Mohammed; Baqui Billah, Syed Muhammad; Saquib, Nazmus; Helmy, Akram; AlJundi, Saadi; Rajab, Tawfik; Enabi, Saed; AlShwaikh, Ahmed; Morhaf, Abdullah; Sherif, Hossam
Summary: Background & aims: Physical and mental well-being following vitamin D supplementation shows contradictory data in the literature. We aimed to explore this more among young and middle-aged Saudi females suffering from vitamin D deficiency by analyzing handgrip strength and self-reported quality of life. Methods: Fifty-eight females with bone or muscle aches attending the outpatient orthopedics clinic of an area hospital were enrolled after informed consent. Each participant filled out the SF-8™ questionnaire for quality of life (QOL) and was assessed for demographic/behavioral data, serum level of 25-hydroxyvitamin D (25(OH)D), and handgrip (HG) for both hands at baseline and 3 months after standard 25(OH)D oral supplementation. Results: The mean age was 31.9 ± 7.3 years; serum 25(OH)D values increased significantly after the oral supplementation (11.28 ± 4.1, range 4.2–22 vs. 23.98 ± 6.81, range 7–41.4 μg/dl, P < 0.001) The handgrip mean for both hands after 25(OH)D supplementation also showed statistically significant higher values (13.24 ± 4.95, range 5–25.33 vs. 17.76 ± 4.39, range 9.5–27.33 kg/m 2, P < 0.001). The SF-8™ QOL questionnaire results showed an overall statistically significant improvement ( P < 0.001). 25(OH)D baseline values predicted muscle weakness; area-under-the-curve was 63% (95% CI: 47–79%) with the best cut-off value at 17.17 μg/dl (sensitivity 64% and specificity 62%). Conclusion: Adult Saudi females showed improved muscle strength and quality of life following standard 25(OH)D oral supplementation. Highlights: Baseline 25(OH)D values predicted muscle weakness with a cut-off value of 17.2 μg/dl. Screening vitamin D deficient patients for muscle weakness and QOL is recommended. Muscle strength and QOL improved following 25(OH)D supplementation.